INOVASI DALAM TEORI PEMBELAJARAN DAN APRESIASI SASTRA DENGAN MODEL INDEX CARD MATCH PADA MAHASISWA PGSD UNPARI - Agung Nugroho (Linggau Journal Science Education (LJSE), 2026)
This study aims to analyze the effectiveness of innovations in learning theory and literary appreciation through the application of the Index Card Match learning model for students of the Elementary School Teacher Education Program (PGSD) at UNPARI. The method used was a quasi-experimental approach with a quantitative approach. The study population included all students taking the Theory and Literary Appreciation course for Elementary School in the 2025/2026 academic year. The research sample was determined through a purposive sampling technique, namely one class selected based on certain considerations as the research subject. Data collection techniques were carried out through essay tests used to measure theoretical understanding and the ability to appreciate children's literature. Data analysis was carried out using descriptive and inferential statistical techniques, including normality tests and hypothesis testing using t-tests. The results of the study showed that there was an increase in students' abilities in understanding theory and appreciating literature after the implementation of the Index Card Match learning model. In addition, the results of the hypothesis testing showed a significant influence of the application of the model on student learning outcomes. This was indicated by increased understanding, activeness, and ability to appreciate literary works. The conclusion of this study is that the Index Card Match learning model is effective as an innovation in learning theory and literary appreciation to improve the understanding and literary appreciation abilities of PGSD students at UNPARI.